Dictionary of alkaloids - Buckingham, J. (CRC Press, 2010)
While some of the most commonly investigated - and most notorious - chemicals in the world are alkaloids, many modern medicines are also based on alkaloid structures. This dictionary categorizes various known alkaloids, presenting concise chemical, structural, and physical data